2009
DOI: 10.3390/ijms10041729
|View full text |Cite
|
Sign up to set email alerts
|

Adenylate Kinase and AMP Signaling Networks: Metabolic Monitoring, Signal Communication and Body Energy Sensing

Abstract: Adenylate kinase and downstream AMP signaling is an integrated metabolic monitoring system which reads the cellular energy state in order to tune and report signals to metabolic sensors. A network of adenylate kinase isoforms (AK1-AK7) are distributed throughout intracellular compartments, interstitial space and body fluids to regulate energetic and metabolic signaling circuits, securing efficient cell energy economy, signal communication and stress response. The dynamics of adenylate kinase-catalyzed phosphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
320
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(329 citation statements)
references
References 269 publications
(631 reference statements)
6
320
0
3
Order By: Relevance
“…Under these conditions, mitochondrial ATP extruded in the cytosol allows AK to transform AMP into ADP that can be readily converted into extra ATP in the mitochondria. In keeping with this interpretation, silencing of the main cellular AK isoforms AK1 and AK2 (27,30) prevents the increase of ATP content above basal levels in Glu Ϫ cells undergoing PARP-1 activation (Fig. 3G).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Under these conditions, mitochondrial ATP extruded in the cytosol allows AK to transform AMP into ADP that can be readily converted into extra ATP in the mitochondria. In keeping with this interpretation, silencing of the main cellular AK isoforms AK1 and AK2 (27,30) prevents the increase of ATP content above basal levels in Glu Ϫ cells undergoing PARP-1 activation (Fig. 3G).…”
Section: Discussionsupporting
confidence: 70%
“…Key enzymes converting AMP back to ADP are AKs (27) that catalyze the AMPϩATP7ADPϩADP reaction in a forward or reverse direction based on the relative concentrations of the nucleotides. AKs are key enzymes involved in intracellular AMP signaling and metabolic regulation (27). We speculated, therefore, that AK activity prevents AMP increase in Glu Ϫ cells given their maintained ATP content during PARP-1 hyperactivation.…”
Section: Effect Of Glucose On Adp and Amp Content During Parp-1mentioning
confidence: 99%
“…In intact cells AMP is a strong metabolic signal that regulates cellular energy production through several signaling pathways including AMP kinase (reviewed in Ref. 31). Therefore, intracellular dialysis of large concentrations of AMP likely causes drastic changes in cellular metabolism that are expected to be cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…6B). In addition, we studied the expression level of transcripts of Ak1 (Adenylate kinase 1) that is involved in the inter-conversion of adenine nucleotides and plays an important role in cellular energy homeostasis [27]. We found that Ak1 mRNA was reduced by approximately 50% in HD hearts (Fig.…”
Section: Transcriptional Remodeling Of Genes Involved In the Synthesimentioning
confidence: 97%